Predictors of patients' preferences for treatments to prevent heart disease. Issue 11 (18th May 2006) - Marshall, T; Bryan, S; Gill, P; Greenfield, S; Gutridge, K
Abstract : Objectives: To determine the relationship between expressed preferences for drug treatment to prevent coronary disease and several participant and general practitioner characteristics among patients attending coronary risk screening. Design: Face-to-face interviews with patients. At the first interview, a researcher asked participants to imagine six scenarios representing different levels of pretreatment five-year coronary risk. In each case they were asked whether they would choose treatment that would reduce their coronary risk by 30% of pretreatment risk. At the second interview participants were told their coronary risk and asked whether they would choose treatment. Sociodemographic variables were collected to investigate their relationship to patients' treatment preferences. Participants: Patients identified as likely to be at high coronary risk were invited to attend for risk screening and to participate in the study. Setting: 13 practices in the West Midlands. Results: Participants' preferences varied widely: at the first interview 112 (55.2%) of 203 participants preferred treatment at 3% five-year coronary risk but 31 (15.3%) preferred no treatment even at 30% five-year coronary risk. Age, sex, education and drug treatment history did not affect preferences, but lower social class was associated with preferring treatment at lower risk. Preferences expressed at the second interview were generally consistent with preferences at the first interview (κ  =  0.510, 95% CI 0.380 to 0.639). Conclusions: Patients attending for coronary risk screening express stable preferences for drug treatment to prevent coronary heart disease. Their preferences vary widely and may be associated with social class.